The Role of Women in Shaping the Future of Technology: Challenges and Opportunities - Tamanna Quraishi; Sajeda Mohammad; Sheeba Raufi; Fatima Naimi (Tinta Emas Institute, 2024)
The role of women in shaping the future of technology has become a critical area of focus in recent years, with efforts aimed at addressing gender disparities and promoting inclusivity in tech fields. The research examines educational barriers, workplace gender biases, mentorship programs, and the impact of female entrepreneurship on innovation within the technology sector. A quantitative research design was employed, utilizing a survey with 120 participants from four faculties—Medical, Computer Science, Social Science, and Education—across different age groups. The data were analyzed using descriptive statistics to uncover patterns and insights. The results indicate that educational barriers, such as the lack of encouragement for women in STEM fields, remain a significant challenge. Gender biases in the workplace were also found to negatively affect career advancement opportunities for women in technology, with participants reporting substantial concerns regarding systemic discrimination. However, mentorship programs were seen as highly effective in encouraging women to pursue careers in technology, and female entrepreneurship was perceived as having a notable impact on innovation within the sector. The findings suggest that while challenges persist, there are emerging opportunities to enhance women’s contributions to technology, particularly through education, mentorship, and support for female entrepreneurs. In conclusion, the study emphasizes the need for continued efforts to address gender inequality in technology fields, with a focus on fostering supportive environments that enable women to thrive in the industry.